'It made me think how I should treat others and how I should help people who need it': The complexities of exploring the impact of Holocaust education. (1st November 2020) - Hale, Rebecca
ABSTRACT: It is generally agreed that learning about the Holocaust has some impact on students. However, discussions about the nature and magnitude of impact tend to be intuition-based rather than evidence-based. This is exacerbated by studies giving insight into how Holocaust education is related to salient variables rather than studies which demonstrate that teaching and learning about the Holocaust directly result in particular outcomes. Additionally, studies have drawn on small samples or presented findings which rely only on participants' own perceptions of impact rather than actual impact measurement. These issues have contributed to a muddled and contestable narrative about impact in this field. This paper explores the complexities of studying the impact of Holocaust education, considers the feasibility of using randomised control trials, and appeals to those working in the field to be mindful of making and accepting spurious claims about impact.